The timeliness of Kelantan local authorities' financial reports / Nur Raihana Mohd Sallem, Noor Emilina Mohd Nasir and Asmah Abd Aziz. - Mohd sallem, Nur raihana; Mohd Nasir, Noor Emilina; Abd Aziz, Asmah (Universiti Teknologi MARA Cawangan Selangor, 2012)
The main objective of this study was to examine audit lag of local authorities in Kelantan. In particular, this study investigated accounts preparation lag, audit lag and the association of audit lag with three factors; types of audit report, number of audit incidents and preparation lag. The findings of the 11-year period showed that only 13.28% financial reports were completed within five months while 2.34% took more than 11 months. Furthermore, this study also revealed that 46.97% of audit lag of local authorities in Kelantan were within requirement of Act 171 which is 10 months. However, there were still 13.64% of audit lag which exceeded 12 months. Finally, the correlation test showed that only preparation lag was significantly associated with audit lag. The results of our study increase the understanding of how Kelantan local authorities manage to prepare their financial report in timely manner.